BIFURCATION, SENSITIVITY AND OPTIMAL CONTROL ANALYSIS OF MODELLING ANTHRAX-LISTERIOSIS CO-DYNAMICS. (2020) - OSMAN, SHAIBU; OTOO, DOMINIC; SEBIL, CHARLES; MAKINDE, OLUWOLE DANIEL
No abstract available